Different Planting Media in Barangan Banana (Musa Acuminata Colla) Breeding in Southeast Aceh - Nico Syahputra Sebayang; Diah Eka Puspita; Surya Basri (Talenta Publisher, 2018)
Many banana plants in Indonesia have been cultivated by the community, one banana plant that has a high potential and has a chance to be developed is barangan banana (Musa acuminata Colla). The aim of this study is to find out the response of the growth of banana suckers using different planting media. This study was conducted in Kumbang Jaya Village of Badar District of Southeast Aceh Regency, which took place from April to June 2017. A non factorial randomized block design (RBD) consisting of 3 levels of treatment with 4 replications was used as a research design in this study. The level of treatment is PM1: soil without mixture, PM2: soil + manure + sand (1: 1: 1) and PM3: soil + husk + sand (1: 1: 1). Parameters observed were plant height aged 2, 4, 6 and 8 weeks after planting (WAP), stem diameter aged 2, 4, 6 and 8 WAP and number of leaves aged 2, 4, 6 and 8 WAP. The results showed that different planting media had a very significant effect on plant height at 8 WAP, number of leaves aged 6 WAP and significantly affected the stem diameter of 8 WAP. But the effect was not significant on plant height aged 2, 4 and 6 WAP, stem diameter aged 2, 4 and 6 WAP and the number of leaves aged 2, 4 and 8 WAP. For plant height, stem diameter and number of leaves aged 2, 4 and 6 WAP, the growth produced by each treatment tends to be the same